Systemic Kras ablation disrupts myeloid cell homeostasis in adult mice - Elena Zamorano-Dominguez; Lucia Morales-Cacho; Rebeca Barrero; Silvia Jiménez-Parrado; Alma Dhawahir; Isabel Hernández-Porras; Lucía Simón-Carrasco; Sara Barrambana; Pian Sun; Ana Galván-del-Rey; Blanca Rosas-Perez; Vasiliki Liaki; et al. (Proceedings of the National Academy of Sciences, 2025)
The KRAS oncogene has been associated with many types of cancer, including pancreatic, lung, and colorectal. For decades, its gene products were thought to be undruggable. However, during the last decade, a large battery of KRAS inhibitors selective against specific mutations (KRAS G12C and KRAS G12D ), panKRAS inhibitors active against all KRAS isoforms, or even panRAS inhibitors, capable of inhibiting the three members of the RAS family, have been developed. In mice, the Kras locus is essential for embryonic development and can sustain adult homeostasis in the absence of Hras and Nras expression. Thus, we considered of interest to interrogate the role of the Kras locus in an experimental system to generate potentially relevant information regarding the use of panKRAS or panRAS inhibitors in the clinic. Here, we report that systemic ablation of Kras expression in adult mice does not induce significant changes in overall survival, body weight, glucose levels, metabolic profile, or heart function. In contrast, flow cytometry and histopathological analyses of organs such as blood, bone marrow, and spleen showed a significant increase of the myeloid lineage leading to myelomonocytic metaplasia. In this context, replacement of the KRAS isoforms by HRAS is sufficient to maintain adult homeostasis, suggesting that the unique properties of the Kras locus are primarily due to its pattern of expression rather than to the activity of its gene products.